ANALYSIS OF THE CURRENT STATE OF THE DEVELOPMENT OF THE TOURISM INDUSTRY AND RESORT AND RECREATION SPHERE OF UKRAINE AND ITS REGIONS - NOD, ORSHOIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Over the last decade, the balanced development of the modern tourism industry and the resort-recreational sphere has been noticeably marked by significant changes. The functioning and effectiveness were affected by several factors: the political situation in the country, regulatory and legal support, COVID-19, military aggression, socio-economic development of the regions and the country in general, etc. The statistical analysis of trends in the development of the tourism industry and the resort and recreation sphere of Ukraine was created by employees of various national and international tourism development agencies. Most of the works are aimed at monitoring the general characteristics of the development of tourism and recreation in Ukraine and abroad, and their systematization from the standpoint of determining new innovative landmarks of regional sustainable development is insufficiently presented, which determines the relevance of the chosen research topic.The method of writing the article is an analysis of the current state of development of the tourism industry and the resort and recreation sphere of Ukraine and its regions. The article examines the current state of development of the tourism industry and the resort and recreation sphere of Ukraine and its regions. The dynamics of GDP indicators and the share of the tourism sector of Ukraine, the gross added value created in the field of tourism, and the dynamics of the number of health and recreation facilities across the regions of Ukraine were analyzed. The grouping of the main resorts and sanatoriums by regions of Ukraine is characterized. It was determined that the current state of tourism and recreation development depends on many global, national, and regional factors. An analysis of the current state of the tourism industry and the resort and recreation sphere is necessary in order to ensure the development of a tourism development strategy taking into account several factors: the political situation in the country, regulatory and legal support, COVID-19, military aggression, socio-economic development of the regions and the country in general, etc. The industry of tourism and resort recreation creates economic and social effects that are closely interconnected. The social effect leads to the improvement of the nation, which is the task of developing human potential, and the economic effect ensures the formation of the gross domestic product. Replacing state expenditures on health care with a more effective source of self-financing for the reproduction of the population's health through the provision of resort and recreation services is becoming critical.
Keywords: tourism; recreation; resorts; recreation facilities; dynamics; region